The impact of ancient Arab civilization in the book of the Old Testament among the Jews - صفية وحيد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Some scholars believe that the Arabian Peninsula is the first cradle of the sons of Shem, and from it the waves of human beings started in all parts of the country as a result of drought, lack of rain, and an increase in the number of people who had no need to take the path of migrations to fertile places. The first Arab tribe to migrate from the Arabian Peninsula in the fourth millennium BC settled in Mesopotamia, and these immigrants were known as (Akkadians), who formed a powerful and sprawling empire that stretched from Mesopotamia in the east to the Mediterranean in the west. When the Jews who lived in some areas of Palestine rebelled against them, the Babylonian King Nebuchadnezzar attacked them in 587 BC, and more than forty thousand of the Jews of Jerusalem were taken as captive to his capital, Babylon, and they stayed there until the year 539 BC. Among them were princes, priests, scribes and intellectuals, and they were dazzled by the greatness of Babylon with its palaces, temples and gardens, and they were also greatly impressed by the intellectual, spiritual and cultural heritage of Babylon. This was reflected in the writings of the Jews later, especially during their writing of their sacred book, where the Jews built their glory on the ancient civilizational codes of Mesopotamia, and the influence of Mesopotamian literature on the literature of the Hebrews appeared, and this influence is what we wanted to monitor in our research.